Características clínico epidemiológicas de pacientes con glaucoma primario - Instituto Regional De Oftalmología JSU - Periodo 2019 - Túllume Flores, Luigi Joseph (2022)
Progressive optic neuropathy characterized by specific changes in the visual field associated with the death of retinal ganglion cells. BACKGROUND: In the literature, the clinical-epidemiological characteristics are described in numerous studies, with some similar results and others that are completely opposite; In the review carried out, no work was found that reports data from our city, which is why the idea of this research arose, a prospective work having been planned, but due to the pandemic it was changed to retrospective. OBJECTIVE To report the main clinical and epidemiological characteristics of patients with primary glaucoma treated at the Regional Institute of Ophthalmology "Javier Servat Univazo" in the period January - December 2019. METHODS Descriptive, retrospective, analytical study, where 1280 patient medical records were reviewed. with primary open-angle and angle-closure glaucoma whose first diagnosis was made in the Glaucoma service in the period January - December 2019. Various parameters will be recorded, such as age, sex, associated refractive error, associated comorbidity, glaucoma severity, among others.